Woody vegetation of Sile and its environs (Istanbul/Turkey) and destruction of the area - (:unkn) unknown (TRIVENI ENTERPRISES, 2015)
The woody vegetation of Sile district (Istanbul/Turkey), and its characteristics in conjunction with its environs are presented in this study. The field studies were performed using classic Braun-Blanquet method during 2003-2010 periods. In the present study three associations, two from forest vegetation and one from maquis vegetation, were characterized in the field. One of these associations is new and its description, typification and syntaxonomy was proposed. Phytosociological and phytoecological features of all three associations were compared with their relatives and related discussion was done accordingly. The associations described in the present study were as follows: Phillyreo-Lauretum nobilis, Smilaco-Castanetum sativae, Fago orientalis-Quercetum ibericae ass. nova. Furthermore, some soil properties such as saturation, organic matter, pH, CaCO3, K2O and P2O5, were analyzed. Relationship between vegetations, their ecological characteristics and protection of these vegetations against biotic pressures are outlined in the present work.
Keywords: Forest vegetation; Phytosociologic; Phytoecologic; Soil analysis; FOREST VEGETATION; DIVERSITY; SYNTAXONOMY; REGION; TURKEY